2019
DOI: 10.1016/j.qref.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence on the long and short run determinants of health expenditure in the Arab world

Abstract: This paper empirically examines the determinants of health care spending for 18 Arab world countries for the period 1995-2015 by using recently developed panel cointegration techniques. We conducted the same estimations for 3 sub-samples, namely high-income, upper-middle-and lower-middle-income countries to reduce the heterogeneity among them. Our empirical findings demonstrate that health care expenditure and its determinants are non-stationary, and revealed the existence of a long run relationship among vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 52 publications
4
25
0
2
Order By: Relevance
“…Another study conducted by Lopreite [9] in Italy found that the government spending on the healthcare sector more respected by the number of elderly people compared to community revenues and life expectancy figures. Research from Barkat [10] found that in the short term, public income was very influential in government expenditure on the health sector. However, on the long runs not only income that significantly affects the issuance of the health sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study conducted by Lopreite [9] in Italy found that the government spending on the healthcare sector more respected by the number of elderly people compared to community revenues and life expectancy figures. Research from Barkat [10] found that in the short term, public income was very influential in government expenditure on the health sector. However, on the long runs not only income that significantly affects the issuance of the health sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first step is to test for CSD among variables using the cross-sectional dependence test (CD) of Pesaran (2004). Then, ignoring CSD among variables might lead to an inconsistent result and give misleading information (Dong et al, 2018;Barkat et al, 2018). Second, we perform the CADF and CIPS test developed by Pesaran (2007) that accounts for CSD.…”
Section: Methodsologymentioning
confidence: 99%
“…Third, in terms of aid effectiveness, the foreign aid fungibility issue may be one of the reasons that reduce aid effectiveness (Feyzioglu et al, 1998). According to Barkat et al (2016), aid is more fungible in middle-income African countries than in the low-income countries due to the higher amount of foreign aid, volatility of donor aid, capacity of absorption, number of donors and the preferences of donors and recipients. Table 2 shows the impacts of the other explanatory variables of agricultural production.…”
Section: Estimating Panel Models With Heterogeneous Slopes and Csd (Imentioning
confidence: 99%
“…The selection of control variables was mainly based on research [39,40], and the availability of control variable data was also considered. The selected variables included: (1) the logarithm of GDP per capita, in order to control the development level of the country; (2) the average saving, in order to control the impact of personal savings; (3) the unemployment rate, in order to control the impact of unemployment on consumer spending; (4) the loan interest rate, in order to control the development of the financial credit market, (5) the M2/GDP indicator, in order to control the expansion of the money market, and (6) the CPI indicator, in order to control domestic consumer inflation.…”
Section: Data Descriptionmentioning
confidence: 99%